Savvy Sheldon feels good as hell - McCoy, Taj (Mira, 2022)
While renovating her house and her life, Savvy Sheldon finds things going not as planned and soon realizes that she should have started her renovation the other way around, beginning with how she sees and loves herself before she can love someone else.